INFLUENCE OF L- LYSINE SULFATE ON CONTAINING OF VITAMINS AND MINERALS IN THE BODY OF BROILER CHICKENS - Andrey Shaposhnikov; Inessa Yakovleva; Irina Nedopekina; Ulyana Krut; Ludmila Zakirova (Research Results in Pharmacology, 2016)
Experimental researches have shownthatthe L-lysine sulfate (the product of microbiological synthesis) has a positive effect on metabolism of vitamins A, E, C in the liver and minerals calcium and phosphorus in the blood and bones of broiler chickens. The dose of L-lysine sulfate of 800 mg∙kg-1 and 1000 mg∙kg-1 weight body has influence on increasing vitamins level in the liver. Was observed, that indexes of calcium and phosphorus are increased in the blood but it’s decreased in the bones of broiler chickens. This results are necessary for Veterinary Pharmacology Consults and official practically using in agricultural sectors of Russian Federation.